Taxonomy of the genus Diochus Erichson (Coleoptera: Staphylinidae, Staphylininae, Diochini) of Papua New Guinea, Vanuatu and Solomon Islands - Huang, Tian; Janák, Jiří; Zhou, Hong-Zhang (Zootaxa, 2024)
This paper presents taxonomic studies of the genus Diochus Erichson, 1839 (Coleoptera: Staphylinidae, Staphylininae, Diochini) from Papua New Guinea, Vanuatu and Solomon Islands. Three new species are described: Diochus elongatus Huang, Janák & Zhou, sp. nov. and D. loebli Huang, Janák & Zhou, sp. nov. from Papua New Guinea, and D. chambrieri Huang, Janák & Zhou, sp. nov. from Papua New Guinea, Vanuatu and Solomon Islands. D. papuanus Cameron, 1939 is redescribed. All species are included in a key to species and are provided with color photos. The new species also with line drawing plates.
Keywords: Animal Distribution; Organ Size; zvířata; Ecosystem; velikost orgánu; Animals; Coleoptera; brouci; rozšíření zvířat; velikost těla; Animal Structures; Female; anatomické struktury zvířat; Melanesia; ekosystém; Papua New Guinea; Male; ženské pohlaví; mužské pohlaví; Papua Nová Guinea; Melanésie; Body Size; Vanuatu